2018
DOI: 10.2214/ajr.17.18739
|View full text |Cite
|
Sign up to set email alerts
|

Acute Nonhemorrhagic Adrenal Infarction in Pregnancy: 10-Year MRI Incidence and Patient Outcomes at a Single Institution

Abstract: Unilateral nonhemorrhagic adrenal infarction was identified in 1.3% of abdominal MRI examinations performed for pregnant women with acute abdominal or flank pain. Knowledge of the MRI characteristics of this entity is important for recognizing it and may prevent further potentially invasive tests, procedures, or missed diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…In the absence of an obvious diagnosis with ultrasound, MRI is the next preferred modality due to its safety in pregnancy. MRI findings of non-haemorrhagic adrenal infarction have only recently been defined in a 10-year single institution study 6. These consist of increased T2 signal intensity of the infarcted adrenal with surrounding oedema and without T1 intensification to suggest lack of haemorrhage, as seen in our patient.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the absence of an obvious diagnosis with ultrasound, MRI is the next preferred modality due to its safety in pregnancy. MRI findings of non-haemorrhagic adrenal infarction have only recently been defined in a 10-year single institution study 6. These consist of increased T2 signal intensity of the infarcted adrenal with surrounding oedema and without T1 intensification to suggest lack of haemorrhage, as seen in our patient.…”
Section: Discussionsupporting
confidence: 50%
“…Although, one author recommends conservative management based on a single case report showing complete resolution of symptoms and uncomplicated perinatal outcome without anticoagulation 9. A more recent case series of four patients with five instances of adrenal infarctions showed that two patients who did not receive anticoagulation had uncomplicated perinatal outcome but the third patient who was discharged without anticoagulation in the 17th week of gestation presented back in her 35th week with contralateral adrenal infarction and was then anticoagulated for 6 months 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute adrenal infarction (AAI) is a rare but serious complication of hypercoagulable conditions such as primary antiphospholipid antibody syndrome or pregnancy [4,5]. CT diagnosis of AAI is based on an enlargement and a low attenuation of the infarcted adrenal gland, sometimes associated with a high attenuation surrounding rim with fat stranding and "capsular sign" [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is logical that these two risk factors together, hypercoagulability of pregnancy and adrenal vein anatomy, may exacerbate blood stasis within the adrenal vein and lead to venous thrombosis. The risk of a thrombosis and consequentially infarction should be considered in non-pregnant patients with a known hyper-coagulable state [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%